Pemanfaatan Biji Kluwih Sebagai Media Alternatif Untuk Pertumbuhan Bibit F0 Jamur Tiram Putih Dan Jamur Merang - Anggraini, Amalia; , Dra. Suparti, M.Si (2017)
Kluwih seeds have a nutritional balance that includes carbohydrates, fats, proteins, and minerals that are good for the body. Kluwih seed contains 9.8 g protein, 5.9 g fat, 52.7 g carbohydrates, 53 mg of calcium, and magnesium 100 mg. This study aims to determine the growth of F0 oyster mushroom and mushroom seeds on kluwih seed media on the growth of mycelium. The research method used is experimental research method with Completely Randomized Design (RAL) with 2 factorial that is kluwih seed treatment and fungus type. Based on the result of the research, the growth media of F0 oyster mushroom and mushroom seeds and the growth of mycelium at the fastest growth on the 7th day on medium mushroom kluwih mushroom (J2M2) has a mycelium diameter of 7.5 cm with a thin mycelium thickness and Mycelium growth is the slowest growth on the 7th day on the medium of kluwih mushroom seed pulp having a diameter of 1 cm mycelium with a thin mycelium thickness in the petri dish. Then it can be concluded that kluwih seeds can be used as a growth medium F0 oyster mushroom and mushroom merang and the best growth on the mushroom pulp kluwih mushroom media. Keywords: kluwih seed, mycelium growth, oyster mushroom and mushroom